Peran Keluarga terhadap Kesehatan Reproduksi Remaja di Kelurahan Uma Sima Kecamatan Sumbawa - Evi Gustia Kesuma; Yunita Yunita; Yunita Lestari (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Adolescent reproductive health is a crucial aspect in creating a physically, mentally, and socially healthy generation. Adolescence is a critical phase in individual development marked by biological, psychological, and social changes, requiring special attention, particularly regarding understanding reproductive health. Unfortunately, many adolescents still have limited knowledge in this area, which can increase the risk of risky behavior, unwanted pregnancy, and sexually transmitted infections. In this context, families play a crucial role as the primary source of education, supervision, and emotional and moral support. This community service activity aims to increase the knowledge and understanding of adolescent reproductive health among families in Uma Sima Village, Sumbawa District. The methods used included interactive counseling, group discussions, and the distribution of educational media in the form of leaflets to families with adolescent children. The activity was conducted over two days and was attended by 30 families. To measure the effectiveness of the activity, pre- and post-tests were conducted to assess the increase in participants' knowledge before and after the activity. The results of the activity showed a significant increase in families' understanding of adolescent reproductive health issues. This was evident in the increase in the average post-test score compared to the pre-test. Furthermore, participants demonstrated high enthusiasm in participating in the activities, actively participating in discussions, and expressing their readiness to provide education to their children at home. In conclusion, this activity was effective in increasing family knowledge and demonstrating the importance of the family's role in preventing adolescent reproductive health issues. It is hoped that similar activities can be conducted on an ongoing basis to create a supportive, open, and communicative family environment that supports adolescent growth and development.